Isolation and characterization of a high ethyl acetate-producing yeast from Laobaigan Daqu and its fermentation conditions for producing high-quality Baijiu. Issue 5 (3rd September 2018) - Fu, Zhilei; Sun, Baoguo; Li, Xiuting; Fan, Guangsen; Teng, Chao; Alaa, Ahmad; Jia, Yingmin
Abstract: A yeast that produces high levels of ethyl acetate was isolated and purified from Laobaigan Daqu by traditional microbial methods and was identified as Wickerhamomyces anomalus by its morphology and 26S rDNA D1/D2 sequence. This strain, YF1503, greatly tolerated ethanol and ethyl acetate. The optimal conditions for producing high levels of ethyl acetate were identified using single factor experiments and response surface methodology. Under these fermentation conditions, strain YF1503 produced 17.35 g/L ethyl acetate, the highest level that has been reported. The presence of alcohol acyltransferase (AAT) activity (8.63 U/L) and changes in the concentrations of ethanol and ethyl acetate in the fermentation broth indicate that strain YF1503 synthesises ethyl acetate using the acyltransferase pathway.